Influence of learning mentoring on mentor effectiveness: case of nursing studies - Rupšienė, Liudmila; Paulikienė, Simona (Social Welfare: Interdisciplinary Approach, 2016)
Despite many arguments for the influence of effective mentoring on training professionals, in practice, the problem of effective mentoring still remains a relevant issue. Based on the theoretical understanding that mentoring can be learnt, the article raises the following problem question: “what is the influence of learning mentoring on mentor effectiveness”? Having selected the case of nursing studies, an anonymous written survey of nursing students and their mentors was conducted in 2014. Statistical data analysis of 441 pairs (of a student and his or her mentor) showed that mentor effectiveness in the case of nursing studies depends on learning mentoring.
Keywords: learning mentoring; mentoring effectiveness; training of nurses